“Impact of economic growth on scientific production in Latin America and the Caribbean based on panel data analysis [version 1; peer review: 2 approved with reservations, 1 not approved] “ - Rivera-Lozada, Oriana (2023)
“Background: The great difference in scientific production among countries, especially in Latin America and the Caribbean, may be related to the economic growth of each nation, but countries with larger economies do not necessarily have higher scientific production. Political changes and unstable economies result in little sustainability of scientific production in the countries in these regions. The purpose of this study was to determine the impact of economic growth on scientific production, measured as the variation in the gross domestic product and the number of scientific publications, in Latin American and Caribbean countries. Methods: The analyzed information was collected from the open data source of the World Bank for the years from 2000 to 2018. The analysis was performed using unbalanced data panel models that cross-sectionally considered the countries of Latin America and the Caribbean and longitudinally considered the period 2000-2018 using grouped regression models, fixed effects models or random effects models. The Hausman test was used to choose between fixed and random effects models. Results: The results of both the random effects models and the fixed effects models demonstrated the negative impact of economic growth on scientific production. This proves that it is necessary to state alternatives to mend and improve the state of scientific production. Conclusion: The present study is relevant because it is one of the first to study the impact of gross domestic product on scientific production in Latin American and Caribbean countries from a longitudinal perspective that also allows evaluating the dynamics of both variables.“